Intellectual Education in Islam: Analysis of Ulu al-Albab Verses in the Qur'an - Nur Firdaw Buerahen; Syarifah Syarifah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2024)
Education is considered one of the primary values in Islam, with particular emphasis on the development of intellectuality. The concept of Ulu al-Albab, which literally means